Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

No matter how hard I try I can not figure out how to factor this: 4a^2-32a+63. Any help please? Thanks so much. Please explain the steps!

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
(2 a-9) (2 a-7)
So take the coefficient on the a squared term and multiply that to 63 you need to find two number (we will call them A and B) such that A * B = 4 * 63 and A + B = -32
you do this with other polynomials but the coefficient on the squared term is usually a 1so most people don't teach it that way.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

You are fabulous. Thank you so much! No matter how hard I tried, I could not understand it. You've made it so much simpler!
Your welcome.
I do have one more question...The two numbers I got were 14 and 18.. How did you get 7 and 9 from that?
znimon is busy at the moment, have you tried to do factor by grouping
|dw:1346462806136:dw|
|dw:1346462837874:dw|
|dw:1346462861944:dw|
|dw:1346462941803:dw|
|dw:1346462966127:dw|
hope that helps
Alternatively, you can set the expression equal to zero to get \[\Large 4a^2-32a+63 = 0\] Now solve for 'a' using the quadratic formula \[\Large a = \frac{-B\pm\sqrt{B^2-4AC}}{2A}\] \[\Large a = \frac{-(-32)\pm\sqrt{(-32)^2-4(4)(63)}}{2(4)}\] \[\Large a = \frac{32\pm\sqrt{1024-1008}}{8}\] \[\Large a = \frac{32\pm\sqrt{16}}{8}\] \[\Large a = \frac{32+\sqrt{16}}{8} \ \text{or} \ a = \frac{32-\sqrt{16}}{8}\] \[\Large a = \frac{32+4}{8} \ \text{or} \ a = \frac{32-4}{8}\] \[\Large a = \frac{36}{8} \ \text{or} \ a = \frac{28}{8}\] \[\Large a = \frac{9}{2} \ \text{or} \ a = \frac{7}{2}\] Now rearrange to get the right sides equal to zero \[\Large a = \frac{9}{2} \ \text{or} \ a = \frac{7}{2}\] \[\Large 2a = 9 \ \text{or} \ 2a = 7\] \[\Large 2a - 9 = 0 \ \text{or} \ 2a - 7 = 0\] Finally, use the zero product property to get \[\Large (2a - 9)(2a - 7) = 0\] So this shows us that \[\Large 4a^2-32a+63 = 0\] factors to \[\Large (2a - 9)(2a - 7)\]
Wow, extraordinarily helpful. Thank you!
yw

Not the answer you are looking for?

Search for more explanations.

Ask your own question